Cross-national variation in occupational sex segregation - Charles, Maria [Verfasser] (My University, 1992)
"I examine the relationship between the occupational distribution of men and women in 25 industrial countries and selected social, economic, and cultural factors. Recent research suggests counterintuitive international patterns of occupational sex segregation: low levels of segregation in some traditional countries like Japan and Italy, and high levels in the "progressive" countries of Scandinavia. I argue that the same economic structures that are associated with women's greater integration into the formal labor force also contribute to a deepening institutionalization of gender within the occupational structure. This may occur through the incorporation of women's traditional tasks into the formal economy, and/or through the hierachical and functional differentitation of economic activity in highly industrial societies. Results indicate that some primary structural charcteristics of modern economies (a relatively large service sector and a large employee class) are associated with greater female concentration in clerical, sales, and service occupations. However, other social ideological environments - partially offset these segregative forces. Furthermore, the actual penetration of egalitarian principles into the labor market appears to be mediated by the structure of interest articulation, with corporatist systems showing greater propensity toward segregation." (author's abstract) ((en)) In dem Beitrag wird der Zusammenhang zwischen der beruflichen Geschlechterverteilung und ausgewählten sozialen ökonomischen und kulturellen Faktoren geprüft. Neuere Untersuchungen deuten auf international gesehen gegensätzliche Muster der Geschlechterverteilung hin: geringere Segregation in einigen eher traditionell orientierten Ländern wie Japan und Italien steht eine hohe Segregation in "progressiven" Ländern wie in Skandinavien gegenüber. Die Ergebnisse des Vergleichs zeigen, dass einige zentrale Strukturmerkmale hochindustrialisierter Gesellschaften (hoher Anteil des Dienstleistungssektors, hoher Anteil von Angestellten) gleichzeitig mit einer starken Konzentration von Frauen in Büro-, Verkaufs- und Dienstleistungsberufen einhergehen. (IAB2)
Internationale Unterschiede der beruflichen Segregation der Geschlechter
Keywords: G 2.4.5 Gender Mainstreaming; P 1.3 Frauen; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; I 2.1.4 Ballungsgebiete; Geschlechterverteilung; Einflussfaktor; Berufsstruktur; Internationaler Vergleich; Frauenerwerbstätigkeit; Segregation; Quantitative Angaben; Industrieländer